2021
DOI: 10.1016/j.annonc.2021.08.2116
|View full text |Cite
|
Sign up to set email alerts
|

LBA3 Pembrolizumab versus placebo after complete resection of high-risk stage II melanoma: Efficacy and safety results from the KEYNOTE-716 double-blind phase III trial

Abstract: Background: Current standard of care for patients (pts) after resection of high-risk stage II melanoma is observation. In the phase 3 double-blind KEYNOTE-716 trial we evaluated pembrolizumab (pembro) versus placebo in pts with resected AJCC-8 stage IIB or IIC melanoma. We present results of the first recurrence-free survival (RFS) interim analysis.Methods: Eligible pts aged !12 years with complete resection of cutaneous stage IIB or IIC melanoma with negative sentinel lymph node biopsy were randomized 1:1 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 0 publications
0
19
0
2
Order By: Relevance
“…At the ESMO congress in September 2021, the CheckMate 716 interim analysis on pembrolizumab in the adjuvant setting for resected stage IIB-IIC melanoma reported that the risk of disease recurrence or death decreased by 35% compared with placebo, with prolonged RFS and a favorable benefit–risk profile. These promising results may indicate that these stage II patients could also benefit from adjuvant immunotherapy, making its approval likely in the near future [ 59 ]. Another study with the targeted therapy encorafenib/binimetinib is currently ongoing [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the ESMO congress in September 2021, the CheckMate 716 interim analysis on pembrolizumab in the adjuvant setting for resected stage IIB-IIC melanoma reported that the risk of disease recurrence or death decreased by 35% compared with placebo, with prolonged RFS and a favorable benefit–risk profile. These promising results may indicate that these stage II patients could also benefit from adjuvant immunotherapy, making its approval likely in the near future [ 59 ]. Another study with the targeted therapy encorafenib/binimetinib is currently ongoing [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given the improved toxicity profile compared with that of ipilimumab, PD-1 blockade has become a standard of care for adjuvant therapy. Recently, adjuvant pembrolizumab received Food & Drug Administration approval for stage-IIb/c melanoma on the basis of its improved RFS compared with that of placebo 104 .…”
Section: Nct04133948mentioning
confidence: 99%
“…Im September 2021 wurde auf dem ESMO-Kongress die erste Interimsanalyse der adjuvanten Phase-3-Studie KEYNOTE-716 vorgestellt 14 , welche den Einsatz von Pembrolizumab im Stadium IIB und IIC gegenüber Placebo überprüft. Dabei zeigte sich das Rezidiv-freie Überleben im Therapiearm signifikant verbessert.…”
Section: Adjuvante Therapieunclassified
“…Im September 2021 wurde auf dem ESMO-Kongress die erste Interimsanalyse der adjuvanten Phase-3-Studie KEYNOTE-716 vorgestellt [14]…”
Section: Pembrolizumabunclassified